Ex Ante Assessment of Returns on Research Investments to Address the Impact of Fusarium Wilt Tropical Race 4 on Global Banana Production - Staver, Charles; Pemsl, Diemuth E.; Scheerer, Lars; Perez Vicente, Luis; Dita, Miguel (Frontiers in Plant Science, 2020)
The spread of Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4), causal agent of Fusarium wilt of banana (FWB), has been projected to reach 17% of the global banana-growing area by 2040 equaling 36 million tons of production worth over US$10 billion. This potential loss has fueled (inter)national discussions about the best responses to protect production and small-scale growers’ livelihoods. As part of a multi-crop ex ante assessment of returns on research investments conducted by the CGIAR Research Program on Roots, Tubers and Bananas (RTB) from 2012-2016, four FWB research options were assessed: i) improved exclusion, surveillance, eradication and containment measures to reduce Foc TR4 spread (ESEC), ii) integrated crop and disease management to facilitate production of partially FWB resistant cultivars on Foc-infested soils (ICDM), iii) conventional breeding of FWB-resistant cultivars (CBRC), iv) genetically modified FWB-resistant cultivars (GMRC). Building on a risk index (Foc scale) predicting the initial occurrence and internal spread of Foc TR4 in 29 countries, an economic surplus model, cost-benefit analysis and poverty impact simulations were used to assess impact under two adoption scenarios. All options yield positive net present values and internal rates of return (IRR) above the standard 10% rate. For the conservative scenario with 50% reduced adoption, IRRs were still 30% for ICDM, 20% for CBRC, and 28% for GMRC. ESEC has IRRs between 11-14%, due to higher costs of capacity strengthening, on-going surveillance, farmer awareness campaigns and implementation of farm biosecurity practices, which could be effective for other diseases and benefit multiple crops. The research investments would reach between 2.7 million (GMRC) and 14 million (ESEC) small-scale beneficiaries across Asia/Pacific, Sub-Saharan Africa and Latin America/Caribbean. The options varied in their potential to reduce poverty, with the largest poverty reduction resulting from CBRC with 850,000 and ESEC with 807,000 persons lifted out of poverty (higher adoption scenario). In the discussion, we address the data needs for more fine-grained calculations to better guide research investment decisions. Our results show the potential of public investments in concerted research addressing the spread of Foc TR4 to yield high returns and substantially slow down disease spread.